Identification and characterization of peptide fragments for the direct and site-specific immobilization of functional proteins onto the surface of silicon nitride - Kumada, Yoichi; Ootsuka, Takeru; Asada, Masashi; Yoshizuka, Saori; Chiyama, Masateru; Sakane, Masayasu; Fida, Hasan M.D.; Sawada, Kazuaki; Okumura, Koichi; Kishimoto, Michimasa (Journal of biotechnology, 2014)
In this study, we successfully identified peptide fragments that have a strong affinity toward the surface of a silicon nitride (SiN) substrate. An E. coli soluble protein, which was preferentially adsorbed onto the surface of a SiN substrate was isolated by 2D electrophoresis, and it was identified as “elongation factor Tu (ELN)” via the peptide MS fingerprinting method. A recombinant ELN that was originally cloned and produced, also maintained its adsorptive ability to a SiN substrate, by comparison with BSA that was used as a control protein. The peptide fragments derived from the recombinant ELN were prepared via 3 types of proteases with different recognition properties (trypsin, chymotrypsin and V8 protease). The peptide mixture was applied to the surface of a SiN substrate, and then, the SiN-binding peptide candidates were isolated and identified. The amino acid sequences of the peptide candidates were genetically fused with the C-terminal region of glutathione S-transferase as a model protein, and the adsorption properties of mutant-type GSTs on the surface of a SiN substrate were directly monitored using a reflectometric interference spectroscopy (RIfS) sensor system. Consequently, among the 8 candidates identified, the genetic fusion of TP14, V821 and CT22 peptides resulted in a significant enhancement of GST adsorption to the surface of the SiN substrate, while the adsorption of a wild-type GST was hardly detectable by RIfS sensor. These peptide fragments were located at the C-terminal region in the aminoacid sequence of recombinant ELN. Interestingly, the sequence with the shortest and strongest SiN-binding peptide, TP14 (GYRPQFYFR), was also found in that of V821 (GGRHTPFFKGYRPQFYFRTTDVTGTIE). The TP14 peptide might be the smallest unit of SiN-binding peptide, and a clarification of the amino acid contribution in TP14 peptide will be the next subject. Three-fold higher enzymatic activities were detected from the SiN substrate immobilized with GST-TP14 and GST-V821 due to a higher density of enzyme through the SiN-binding peptides. Thus, the SiN-binding peptides identified in this study will be considerably useful for the immobilization of target proteins with high density and biological activity onto the surfaces of SiN substrates, and these will be applicable to the task of coating proteins onto the surface of SiN-based RIfS sensors and semiconductors.